Effect of Smoking Using Smoke Flavorings on Several Characteristics of Farmed Sea Bass (Dicentrarchus labrax) Fillets and on their Evolution During Vacuum‐Packed Storage at Refrigeration Temperature. Issue 2 (6th June 2016) - Vidal, Natalia P.; Goicoechea, Encarnación; Manzanos, María J.; Guillén, María D.
Abstract: Farmed sea bass ( Dicentrarchus labrax ) fillets were smoked using one oil‐based and two aqueous smoke flavorings. The headspace of the smoked products was studied by solid‐phase microextraction followed by gas chromatography/mass spectrometry (SPME‐GC/MS). The effect of smoking on several quality and safety characteristics of the fillets and on their evolution during vacuum‐packed storage at refrigeration temperature was commented on. Special attention was paid to shelflife length. It was proved that microorganisms able to produce spoilage oxygenated metabolites did not grow in any of the smoked fillets; however, in those smoked with the oily flavoring the growth of microorganisms able to produce sulphur derivatives was observed after 20–25 days of storage. Among the smoked products, great differences were observed in relation to odor, color, texture, safety, and also in their evolution during vacuum‐packed storage at refrigeration temperature; no differences were evidenced regarding oxidation derived compounds. Practical Applications: Farmed European sea bass is widely available on the market, its supply being on many occasions greater than its demand. The results of this study could be of great interest for the seafood industry because it was demonstrated that smoking of farmed sea bass fillets with smoke flavorings could be an interesting alternative method of offering ready‐to‐eat sea bass products to consumers. Nevertheless, it was evidenced that many different aspects of this kind of processing should be carefully addressed to obtain a safe ready‐to‐eat product with optimized sensory properties, and as long a shelflife as possible.